Digital Arts and Entertainment
DOI: 10.4018/978-1-4666-6114-1.ch074
|View full text |Cite
|
Sign up to set email alerts
|

Capturing and Conveying Chamorro Cultural Knowledge Using Social Media

Abstract: The Chamorro people have a long history and rich cultural traditions that have survived the affects of colonization and loss of political control. However, these traditions are in danger of being lost if they are not passed from one generation to the next. The purpose of this study is to understand if information and communication technologies, specifically social media, are used to capture and convey Chamorro cultural knowledge. Two data collection methods were used to understand the type(s) of Chamorro cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the exploration of #pugua, there were depictions of Chamorro culture such as dance, art, and festivals without the display of betel nut in the Instagram content. As prior work has demonstrated that Chamorros use social media to learn, capture, and preserve their culture [ 59 ], public health interventions should carefully consider how their visual messages link betel nut content on Instagram to Chamorro cultural identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the exploration of #pugua, there were depictions of Chamorro culture such as dance, art, and festivals without the display of betel nut in the Instagram content. As prior work has demonstrated that Chamorros use social media to learn, capture, and preserve their culture [ 59 ], public health interventions should carefully consider how their visual messages link betel nut content on Instagram to Chamorro cultural identification.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the NHPI population faces challenges in maintaining their unique languages and cultures. Previous research has shown that Pacific Islander communities value social media as a way to preserve culture and indigenous knowledge [ 58 , 59 ]. Betel nut use is closely tied to culture in Guam [ 47 , 51 , 60 , 61 ] and throughout the USAPI [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%